2022
DOI: 10.3390/land11101771
|View full text |Cite
|
Sign up to set email alerts
|

Responses of NDVI to Climate Change and LUCC along Large-Scale Transportation Projects in Fragile Karst Areas, SW China

Abstract: The fragile karst habitat is extremely sensitive to human activities such as large-scale engineering construction. To explore the influence of the construction and operation of the GH (Guiyang-Huangguoshu) highway on the vegetation within a certain range and the response of NDVI to climate factors, Landsat data were used to synthesize annual NDVI maps using the maximum value compositing method. Trend, correlation, and coefficient of variation analyses were performed. The results demonstrate that: (1) During th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Correlation analysis was conducted to quantitatively examine the impact of AT0 on vegetation. Here, we chose 0.4 and 0.6 as the thresholds of the correlation coefficient : low correlation , moderate correlation and high correlation [ 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Correlation analysis was conducted to quantitatively examine the impact of AT0 on vegetation. Here, we chose 0.4 and 0.6 as the thresholds of the correlation coefficient : low correlation , moderate correlation and high correlation [ 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, a comparative analysis of the response of NDVI to climate in ecological background areas and core areas is conducted, drawing the conclusion that the Lanzhou-Xinjiang railway project has a certain impact on NDVI along the route. Wu et al (Wu et al, 2022) conducted a study on the Guiyang-Huangguoshu Expressway, exploring the impact of large-scale engineering construction on Frontiers in Environmental Science frontiersin.org vegetation within a certain range and its response to climatic factors. They concluded that the construction of expressways significantly affects the surrounding vegetation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also shown that urbanization leads to an increase in NLI, which has a significant negative correlation with NDVI [18]. Furthermore, the increase in construction projects, such as highways and railways, also has a profound impact on the dynamic changes of vegetation along transportation lines [49]. Therefore, low or decreasing values of vegetation NPP were also observed.…”
Section: Interactions Between Climate Change and Human Activities On Nppmentioning
confidence: 91%